2018
DOI: 10.1245/s10434-018-6404-y
|View full text |Cite
|
Sign up to set email alerts
|

Major Reduction in Axillary Lymph Node Dissections After Neoadjuvant Systemic Therapy for Node-Positive Breast Cancer by combining PET/CT and the MARI Procedure

Abstract: Combining pre-NST axillary staging with PET/CT and post-NST staging with the MARI procedure resulted in an 82% reduction of ALNDs for cN + breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…However, advancements of imaging have made physical examination an indispensable component of accurate response evaluation that includes modalities such as two-dimensional and three-dimensional mammography ultrasound, magnetic resonance imaging, nuclear medicine techniques (positron emission tomography, PET), fusion techniques (PET-CT, PET-MRI), as well as others (eg, optical imaging). [23][24][25][26]…”
Section: Introductionmentioning
confidence: 99%
“…However, advancements of imaging have made physical examination an indispensable component of accurate response evaluation that includes modalities such as two-dimensional and three-dimensional mammography ultrasound, magnetic resonance imaging, nuclear medicine techniques (positron emission tomography, PET), fusion techniques (PET-CT, PET-MRI), as well as others (eg, optical imaging). [23][24][25][26]…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, most of the patients received direct locoregional radiotherapy without ALND. Subsequently, the authors reported an 82% reduction of ALND for node-positive breast cancer patients (52).…”
Section: Imaging the Lymph-node Metastasesmentioning
confidence: 99%
“…The improvement in survival is more likely to occur in triple negative breast cancer, and in human epidermal growth factor 2 (HER2)-positive breast cancer, particularly when trastuzumab is added to the treatment regimen. The patients who achieve axillary pCR, show better loco-regional and survival outcomes, irrespective of the primary tumor response [45710111213141516]. NAT also provides adequate time for genetic testing, and planning for breast reconstruction, when indicated.…”
mentioning
confidence: 99%
“…In terms of prognosis, the response of the axillary nodes to NAT is known to be a more important factor, than the initial axillary status. The false-negative rates (FNRs) of SLNB after NAT range from 5% to 30%, but these FNRs can be reduced to less than 10% when the dual technique for SLN localization is used, and when more than two LNs can be dissected and examined [68101118192021].…”
mentioning
confidence: 99%
See 1 more Smart Citation